A COMPARATIVE STUDY ON COGNITIVE IMPAIRMENT AMONG ADULTS WITH TYPE 2 DIABETES MELLITUS - Dr. Ankeeta R Vispute (PT); Dr. Larissa A Dsouza (PT) (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Context: Cognitive impairment is a relatively less known and less addressed complication of diabetes. It is a concern because it adversely affects disease self-management resulting in further complications. The incidence of cognitive impairment in adults with diabetes has been demonstrated in a small number of research, particularly when using the MoCA (The Montreal Cognitive Assessment) score, which assesses various domains of cognition.Aims: The aim of the study is to investigate the prevalence of cognitive impairment in adults with type 2 diabetes mellitus and to identify other potential predictors for cognitive impairment. Settings and Design: Comparative study in non-diabetics and diabeticsMethods and Material: 60 people participated in the study. They were further divided into Non-Diabetics (Group A) and Diabetics (Group B). The MoCA score was used to screen for cognitive impairment.Statistical analysis used: Statistical analysis was done using Microsoft Excel and SPSSv.29. Subjects with cognitive impairment did not show significant association with disease characteristics such as duration of diabetes [P 0.240] and control of diabetes [P 0.192]. Results: Most of the diabetic population were females that had cognitive impairment. The total MoCA score in diabetics [mean- 21] was less compared to the non-diabetic patients [mean-28]. The diabetics also scored lower on every domain of MoCA when compared to the non-diabetic group. However, not all domains were affected the same. Conclusions: This study concludes that cognitive impairment was present in most of the diabetic population. Duration of diabetes and Control of diabetes did not show an association with cognitive impairment.